The Influence of Macronutrient Intake towards Intestinal Mucus Production - Rimba, Phoebe Anadita; Lumbantobing, Erika; Carol, Lioni; Rahardja, Ritchie (Indonesia International Institute for Life Sciences, 2022)
Intestinal mucus layer plays a crucial role in protecting the epithelium layer and acts as a barrier to separate the epithelium layer from pathogenic microorganisms. The mucus is synthesized by the goblet cells located in the epithelium layer. The production of mucus inside the goblet cells is regulated by the expression of mucin gene family, such as MUC2 for the mucus production in jejunum, ileum, and colon. Recent studies had suggested the influence of macronutrient intake, such as carbohydrate and fat, in mucus production. High fiber diet and resistant starch consumption were found to positively affect mucus production through upregulating mucin gene expression. Meanwhile, high saturated fat diet was found to negatively affect mucus production by promoting ER stress and downregulating epithelial differentiation transcription factor (KLF4). Nonetheless, a low saturated fat diet was found to upregulate mucin expression. Unsaturated fat diet (oleic acid, linoleic acid, EPA, and DHA), on the other hand, decreased mucin expression by disrupting epithelial differentiation transcription factors (HATH1 and TLR4). Studies on the effect of dietary intake on mucus production are still limited, especially in the underlying molecular pathway. Therefore, further research on the molecular pathway on the effect of dietary intake on mucus production needs to be performed.